2009
DOI: 10.1021/ac901350a
|View full text |Cite
|
Sign up to set email alerts
|

Blood Species Identification for Forensic Purposes Using Raman Spectroscopy Combined with Advanced Statistical Analysis

Abstract: Forensic analysis has become one of the most growing areas of analytical chemistry in recent years. The ability to determine the species of origin of a body fluid sample is a very important and crucial part of a forensic investigation. We introduce here a new technique which utilizes a modern analytical method based on the combination of Raman spectroscopy and advanced statistics to analyze the composition of blood traces from different species. Near-infrared Raman spectroscopy (NIR) was used to analyze multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
108
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 142 publications
(109 citation statements)
references
References 19 publications
1
108
0
Order By: Relevance
“…Fluorescence and Raman spectroscopies are among the most promising nondestructive methods for confirmatory identification of body fluids [4][5][6][7][8][9][10][11][12]. The less sensitive Raman spectroscopy in comparison with fluorescence has higher selectivity and specificity to biochemical species and could potentially be useful in resolving mixtures of multiple body fluids with minimal sample preparation or manipulation [4][5][6][7][8][9][10][11]13]. We have recently demonstrated that the combination of Raman spectroscopy and advanced statistics can potentially discriminate human and animal blood traces [13,14].…”
Section: Open Accessmentioning
confidence: 99%
See 2 more Smart Citations
“…Fluorescence and Raman spectroscopies are among the most promising nondestructive methods for confirmatory identification of body fluids [4][5][6][7][8][9][10][11][12]. The less sensitive Raman spectroscopy in comparison with fluorescence has higher selectivity and specificity to biochemical species and could potentially be useful in resolving mixtures of multiple body fluids with minimal sample preparation or manipulation [4][5][6][7][8][9][10][11]13]. We have recently demonstrated that the combination of Raman spectroscopy and advanced statistics can potentially discriminate human and animal blood traces [13,14].…”
Section: Open Accessmentioning
confidence: 99%
“…The less sensitive Raman spectroscopy in comparison with fluorescence has higher selectivity and specificity to biochemical species and could potentially be useful in resolving mixtures of multiple body fluids with minimal sample preparation or manipulation [4][5][6][7][8][9][10][11]13]. We have recently demonstrated that the combination of Raman spectroscopy and advanced statistics can potentially discriminate human and animal blood traces [13,14]. Raman scattering is a powerful qualitative and quantitative analytical method based on a process where incident monochromatic photons interact with a sample to produce scattered photons with an energy distribution characteristic of molecular structure [15][16][17].…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…Although all blood stains were detected by these three techniques based on their characteristic spectral signal, the extreme similarity among the blood spectra of the three species frustrated the aim of distinguishing them, either by UV-Vis, IR or Raman spectroscopy. This challenging purpose regarding blood species discrimination was subsequently tackled by Lednev's group, by using Raman spectroscopy followed by chemometric analysis [28,29]. In this respect, chemometric analysis such as PCA enabled the discrimination of blood species based on slight spectral differences, differences that are hardly visible or even unnoticed for the naked eye but highly significant by chemometric procedures [28].…”
Section: Vibrational Spectroscopy In Promising Approaches For Body Flmentioning
confidence: 99%
“…This challenging purpose regarding blood species discrimination was subsequently tackled by Lednev's group, by using Raman spectroscopy followed by chemometric analysis [28,29]. In this respect, chemometric analysis such as PCA enabled the discrimination of blood species based on slight spectral differences, differences that are hardly visible or even unnoticed for the naked eye but highly significant by chemometric procedures [28]. Thereby, the differentiation of blood from several species (up to 12) including human, dog, cat, cow, horse, pig and chicken, amongst others, has been successfully achieved [29].…”
Section: Vibrational Spectroscopy In Promising Approaches For Body Flmentioning
confidence: 99%